Applying the driving force-state-response framework and earth observation in evaluating environmental impacts of urban expansion: the case of Riyadh City, Saudi Arabia - Aina, Yusuf Adedoyin (My University, 2022)
The rate of urbanization is unprecedented. Over half of the global population is already residing in urban areas. Future growth is expected to occur in Africa and Asia. Therefore, African and Asian cities are gaining attention on how to monitor and accommodate the impending growth in a sustainable way. Different models have been developed for benchmarking and monitoring sustainable development. However, most of them require adequate spatial data for developing an effective monitoring system. Remote sensing has intensively been used to contribute, with up-to-date data, towards urban sustainability. This study explored the use of the Driving force-State-Response model with satellite derived data in assessing environmental sustainability. The Riyadh city of Saudi Arabia was used as a case study because it is a region that has not been adequately investigated in the literature and one of the fastest growing cities in the Middle East. First, the study provides an overview of the different urban sustainability assessment models and the use of remote sensing data to bridge the data gap as well as the challenges and possible areas of future research. The results indicated the need to address the challenges of uncertainty, getting a “one size fits all indicator” and linking with SDG. Second, the study provides an overview of the urban governance and policies that shaped the development of Riyadh city and the effects of the policies on the sustainability of the city. It examined the recent changes in urban governance in Riyadh and how they might promote urban sustainability in the city. This was carried out by a review of the literature and government publications on urban governance and policy changes in the city. The results highlighted gaps in urban governance, which need to be bridged. v Third, the study explored the techniques of land use classification by comparing spectral angle mapping (SAM), band ratioing and spectral mixture analysis (SMA). The results indicated that the SMA was the most accurate technique and was more amenable for use in the Vegetation-Impervious Surface-Soil model compared to SAM or band ratioing. The usefulness of the Urban Field Percentage of Landscape (UFPLAND) metric in analysing the diffusion and coalescence process of urban expansion was also explored. The results of the analysis revealed that UFPLAND was suitable for the monitoring of the urban process. Riyadh city’s spatial growth followed the diffusion process from 1972 to 1995 and thereafter, the urban expansion in Riyadh has been going through the coalescence process. Fourth, the study examined the environmental impacts of urbanization in Riyadh by testing and comparing the outputs of normalisation methods and a geographical random forest algorithm. The results indicated that one of the normalisation methods (normalised ratio scale) was not successfully computed and the mean normalised LST values in Riyadh had a decreasing trend contrary to the increasing minimum LST values (15°C in 1985 to 32°C in 2015). The results of the geographical random forest showed the influence of land use types and socioeconomic factors on LST in Riyadh. The study concludes that the DSR framework is suitable for urban sustainability assessment, but further research is needed in providing more remote sensing-based data to further reduce the data gap and in standardizing the indicators for usage across different locations and times. Keywords: driving force-state-response framework, land-use/-cover change, sustainability assessment, urban governance, urban heat island, particulate matter
A thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy in Geography and Environmental Studies to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2022